Trabalhadores migrantes no corte da cana-de-açúcar: precarização e exploração do trabalho - Pinheiro, Nataly de Sousa (2013)
This paper has as object of study the analysis of the production relations in the cutting of sugar cane. For this study, the labor of the sugar cane cutter is embodied as a central element, since his activity faithfully portraits the capital-labor contradiction, permeated by intense exploitation and precariousness of the working class. Thus, the research aims as general objective the understanding of the labor relations that permeate the inherent productive process to the seasonal migrant workers, particularly the life conditions and the production of workers of Paraiba that migrate from the city of Tavares, countryside of Paraiba, to the state of São Paulo. Given the theoretical perspective that guides this analysis, a brief study about the emergence, development and central elements of capitalism was performed, to get to the current economic conjuncture, which is characterized by the productive restructuring and flexibility of production. From there, it is discussed the characteristics inherent in the sugar cane agroindustry, in order to grasp the economic, political and social determinations to which the migrant workers are subjected to. Methodologically grounded in a Marxist perspective, the totality of the category references all the research. This, in our view, it‟s essential to the apprehension of the development that will be analyzed here, in which is central the exploitation and precariousness to which the migrant cane cutter are subjected. The procedures that we used seek, by theoretical foundations, to apprehend the reality under analysis. In this way, we have developed an extensive bibliographic research, as we also conducted an empirical research that allowed us a greater approach to the reality of the sugar cane cutting workers, more specifically those that migrate from the state of Paraiba to others regions of the country, because we work with the hypothesis that the fact of being away from their families and the social context to which they are used to living, contributes to worsen the living conditions, be that objectively or subjectively. The research revealed that the fact that the sugar cane cutters are migrants aggravates the exploitation and precariousness of labor, characteristics that are present throughout the process of expansion and development of the capitalistic way of production.